Implementation Of Asean Homestay Standard Criteria On Homestay Management In Loha Tourism Village, West Manggarai Regency - yohana Etheldreda Ine Dae; Claudia Dwi Martina; Gregorius Antariksa Berybe; Dewi Sartika Umul; Agustina Ratna Mbu (Pusat Penelitian dan Pengabdian Masyarakat Politeknik eLBajo Commodus, 2023)
The availability of homestays as tourist accommodation developed in Loha Tourism Village, West Manggarai Regency, is one of the potential attractions. However, in order to assure the quality of tourists services, homestays must be managed in compliance with generally accepted standards, such as the Asean Homestay Standard. Therefore, this study aims to analyze the suitability between the content of the standards in the Asean Homestay Standard and its application in the management of homestays in the tourist village of Loha. The method used in this research is qualitative with an exploratory approach. The results show that the total assessment score for the application of Asean Homestay Standards in accordance with the factual conditions of homestay management in Loha Tourism Village is 34 points with a presentation of 37%. This means that homestays in Loha Tourism Village are in the fair category. The highest score is obtained from the assessment of the activity criteria by 9%, and the lowest score is obtained from the assessment of the security and safety criteria by 2%. Thus, it is necessary to improve the quality of the human resources of the community and homestay managers to be able to maximize the tourism potential of the Loha tourism village.